THE IMPORTANCE OF BIOETHICAL KNOWLEDGE FOR FUTURE PHYSICIAN - Guzal Mardiyeva Karimovna (Лучшие интеллектуальные исследования, 2024)
Introduction: In today's world of advanced medical technology and complex ethical dilemmas, it is crucial for physicians to possess a deep understanding of bioethics. This article explores the significance of bioethical knowledge for physicians in contemporary medicine. Bioethics is a field that addresses the ethical implications of advances in medical science and technology. It encompasses issues such as patient autonomy, confidentiality, end-of-life decisions, genetic engineering, and research ethics. For physicians practicing in the modern healthcare system, having a solid foundation in bioethical knowledge is essential for providing high-quality and morally sound patient care.